Worldwide comparison of survival from childhood leukaemia for 1995–2009, by subtype, age, and sex (CONCORD-2): a population-based study of individual data for 89 828 children from 198 registries in 53 countries. Issue 5 (May 2017) - Bonaventure, Audrey; Harewood, Rhea; Stiller, Charles A; Gatta, Gemma; Clavel, Jacqueline; Stefan, Daniela C; Carreira, Helena; Spika, Devon; Marcos-Gragera, Rafael; Peris-Bonet, Rafael; Piñeros, Marion; Sant, Milena; et al.
Summary: Background: Global inequalities in access to health care are reflected in differences in cancer survival. The CONCORD programme was designed to assess worldwide differences and trends in population-based cancer survival. In this population-based study, we aimed to estimate survival inequalities globally for several subtypes of childhood leukaemia. Methods: Cancer registries participating in CONCORD were asked to submit tumour registrations for all children aged 0–14 years who were diagnosed with leukaemia between Jan 1, 1995, and Dec 31, 2009, and followed up until Dec 31, 2009. Haematological malignancies were defined by morphology codes in the International Classification of Diseases for Oncology, third revision. We excluded data from registries from which the data were judged to be less reliable, or included only lymphomas, and data from countries in which data for fewer than ten children were available for analysis. We also excluded records because of a missing date of birth, diagnosis, or last known vital status. We estimated 5-year net survival (ie, the probability of surviving at least 5 years after diagnosis, after controlling for deaths from other causes [background mortality]) for children by calendar period of diagnosis (1995–99, 2000–04, and 2005–09), sex, and age at diagnosis (<1, 1–4, 5–9, and 10–14 years, inclusive) using appropriate life tables. We estimated age-standardised net survival for international comparison of survival trends for precursor-cell acute lymphoblastic leukaemia (ALL) and acute myeloid leukaemia (AML). Findings: We analysed data from 89 828 children from 198 registries in 53 countries. During 1995–99, 5-year age-standardised net survival for all lymphoid leukaemias combined ranged from 10·6% (95% CI 3·1–18·2) in the Chinese registries to 86·8% (81·6–92·0) in Austria. International differences in 5-year survival for childhood leukaemia were still large as recently as 2005–09, when age-standardised survival for lymphoid leukaemias ranged from 52·4% (95% CI 42·8–61·9) in Cali, Colombia, to 91·6% (89·5–93·6) in the German registries, and for AML ranged from 33·3% (18·9–47·7) in Bulgaria to 78·2% (72·0–84·3) in German registries. Survival from precursor-cell ALL was very close to that of all lymphoid leukaemias combined, with similar variation. In most countries, survival from AML improved more than survival from ALL between 2000–04 and 2005–09. Survival for each type of leukaemia varied markedly with age: survival was highest for children aged 1–4 and 5–9 years, and lowest for infants (younger than 1 year). There was no systematic difference in survival between boys and girls. Interpretation: Global inequalities in survival from childhood leukaemia have narrowed with time but remain very wide for both ALL and AML. These results provide useful information for health policy makers on the effectiveness of health-care systems and for cancer policy makers to reduce inequalities in childhood cancer survival. Funding: Canadian Partnership Against Cancer, Cancer Focus Northern Ireland, Cancer Institute New South Wales, Cancer Research UK, US Centers for Disease Control and Prevention, Swiss Re, Swiss Cancer Research foundation, Swiss Cancer League, and the University of Kentucky.